The Impact of Online Social Activities on Public Spaces in the Digital era - A Case Study of Guochuang Park in Nanjing - He, Qianhui (AESOP, 2024)
In the digital era, public spaces are not only significant venues for daily recreational experiences in the physical world but also the focus of online social platforms. This study, using Guochuang Park in Nanjing, China, as a case study, to explore how online social activities influence the production of virtual spaces on social media platforms and the vitality and landscape of physical public spaces. The research indicates that users on the platform establish new social relationships and virtual spaces through online social activities. Additionally, platform activities can inject vitality into physical spaces but may also lead to some social and spatial issues. Consequently, this study advocates for urban planning to accommodate digital activities while preserving the significance of physical spaces. Keywords: Social Media Platform, Online Social Activities, Public Space Vitality, Production of Space, Local Culture
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024